2016
DOI: 10.1002/lio2.22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular insights into adenoid cystic carcinoma: Neural crest‐like stemness as a target

Abstract: ObjectivesThis review surveys trialed therapies and molecular defects in adenoid cystic carcinoma (ACC), with an emphasis on neural crest‐like stemness characteristics of newly discovered cancer stem cells (CSCs) and therapies that may target these CSCs.Data SourcesArticles available on Pubmed or OVID MEDLINE databases and unpublished data.Review MethodsSystematic review of articles pertaining to ACC and neural crest‐like stem cells.ResultsAdenoid cystic carcinoma of the salivary gland is a slowly growing but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 224 publications
(480 reference statements)
1
13
1
Order By: Relevance
“…We confirmed that ACC cultures maintained MYB fusions found in xenografts or primary tumors and identified a novel MYB fusion to a non-coding RNA. We demonstrated that ACC-CSC that we characterized earlier as SOX10+/CD133+ (17,51) also express CD24 and CD44 as well as signaling molecules commonly found in CSCs, STAT3 and β-catenin. To develop a new platform for drug screening with the goal to develop effective and specific therapies for ACC, we optimized ACC-CSC purification from mixed mouse/human cell cultures and created a novel ACC-CSC-initiated orthotopic model for pre-clinical studies.…”
Section: Discussionmentioning
confidence: 62%
“…We confirmed that ACC cultures maintained MYB fusions found in xenografts or primary tumors and identified a novel MYB fusion to a non-coding RNA. We demonstrated that ACC-CSC that we characterized earlier as SOX10+/CD133+ (17,51) also express CD24 and CD44 as well as signaling molecules commonly found in CSCs, STAT3 and β-catenin. To develop a new platform for drug screening with the goal to develop effective and specific therapies for ACC, we optimized ACC-CSC purification from mixed mouse/human cell cultures and created a novel ACC-CSC-initiated orthotopic model for pre-clinical studies.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, 80%‐90% patients with ACC of the head and neck die within 10‐15 years after diagnosis . Because of its clinical features and histological variations, ACC has been described as a “paradox” and “one of the most biologically destructive and unpredictable tumors of the head and neck” …”
Section: Introductionmentioning
confidence: 99%
“…7 Because of its clinical features and histological variations, ACC has been described as a "paradox" and "one of the most biologically destructive and unpredictable tumors of the head and neck". 8,9 The selection of proper markers for predicting diagnosis and prognosis of ACC is meaningful and urgent. In 2009, a fusion between the myeloblastosis (MYB) and nuclear factor I/B (NFIB) genes, resulting from t(6;9)(q22-23;p24) translocation, was firstly identified in all 11 ACCs studied by Persson et al 7 The fusion was found to be associated with high 5 0 -MYB gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that SOX10, a master regulator of neural stem cells and highly specific marker of Schwann cells and melanocytes, is overexpressed in clinical ACC and BBC specimens as a part of conserved gene signature. Furthermore, we identified substantial overlaps between the SOX10 gene signatures in BBC, ACC, and neuroectodermal cancers (melanoma, neuroblastoma, and glioma) suggesting that SOX10 and its gene signature demarcate CSC with common properties in cancers with similar cell origin 14, 75 . Subsequently, we focused on ACC to demonstrate that SOX10+ cells purified from ACC tissue express CD133, a neural and cancer stem cell surface marker 7679 , and activate signaling pathways and genes characteristic for NSC, such as NOTCH1, FABP7, etc 19 , 75 .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we identified substantial overlaps between the SOX10 gene signatures in BBC, ACC, and neuroectodermal cancers (melanoma, neuroblastoma, and glioma) suggesting that SOX10 and its gene signature demarcate CSC with common properties in cancers with similar cell origin 14, 75 . Subsequently, we focused on ACC to demonstrate that SOX10+ cells purified from ACC tissue express CD133, a neural and cancer stem cell surface marker 7679 , and activate signaling pathways and genes characteristic for NSC, such as NOTCH1, FABP7, etc 19 , 75 . This novel SOX10+/CD133+ CSC population, which we named ACC-CSC, possessed stem cell properties, such as the ability to form spheroids in culture and initiate tumors with ACC histology in nude mice 19 .…”
Section: Discussionmentioning
confidence: 94%